Magnetic Nanoparticles@Metal-Organic Framework Composites as Sustainable Environment Adsorbents. (27th October 2019) - Zhao, Gege; Qin, Nianqiao; Pan, An; Wu, Xiaoyan; Peng, Chuanyi; Ke, Fei; Iqbal, Mudassar; Ramachandraiah, Karna; Zhu, Jing
Abstract : Metal-organic frameworks (MOFs) are an intriguing class of porous inorganic-organic hybrid networks synthesized from metal ions with multidentate organic ligands. MOFs have uniform and tunable cavities and tailorable chemistry, making them promising materials for hazardous component removal from the environment. Controllable integration of magnetic nanoparticles (NPs) and MOFs is leading to the creation of many novel multifunctional MOF-based composites, which exhibit advanced performance that is superior to both of the individual units. This review summarizes the recent significant advances in the development of MOF-based magnetic heterostructure materials for the removal of hazardous contaminants from the environment. The successful methods reported till date for the magnetic MOF synthesis are also provided. In the final section, we provide our views on the future development of the magnetic MOF heterostructure materials for the pollution management.